A systematic review of basic life support training targeted to family members of high-risk cardiac patients. (August 2016) - Cartledge, Susie; Bray, Janet E.; Leary, Marion; Stub, Dion; Finn, Judith
Abstract: Aim: Targeting basic life support (BLS) training to bystanders who are most likely to witness an out of hospital cardiac arrest (OHCA) is an important public health intervention. We performed a systematic review examining the evidence of the effectiveness of providing BLS training to family members of high-risk cardiac patients. Methods: A search of Ovid MEDLINE, CINAL, EMBASE, Informit, Cochrane Library, Web of Science, Scopus, ERIC and ProQuest Dissertations and Theses Global was conducted. We included all studies training adult family members of high-risk cardiac patients regardless of methods used for cardiopulmonary resuscitation (CPR) or BLS training. Two reviewers independently extracted data and evaluated the quality of evidence using GRADE (Grades of Recommendation, Assessment, Development and Evaluation). Results: We included 26 of the 1172 studies identified. The majority of studies were non-randomised controlled trials ( n = 18), of very low to moderate quality. Currently, there is insufficient evidence to indicate a benefit of this intervention for patients; largely because of low numbers of OHCA events and high loss to follow-up. However, the majority of trained individuals were able to competently perform BLS skills, reported a willingness to use these skills and experienced lower anxiety. Conclusion: Whilst there is no current evidence for improvement in patient outcomes from targeted BLS training for family members, this group are willing and capable to learn these skills. Future research may need to examine longer periods of follow-up using alternate methods (e.g. cardiac arrest registries), and examine the effectiveness of training in the modern era.